1960
DOI: 10.1084/jem.111.4.573
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Antibody Formation by Peritoneal Exudate Cells in Vitro

Abstract: Cells from peritoneal exudates of rabbits sacrificed 3 days after an intraperitoneal injection of sterile mineral oil were grown in tissue cultures in medium 199 (75 per cent); normal rabbit serum (25 per cent). Antibody produced by the cells was assayed by an hemagglutination technique in which the antigens used were adsorbed to formalinized tanned sheep erythrocytes. These sensitized cells agglutinate in the presence of antibody specific to the adsorbed antigen. It has been demonstrated that: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1961
1961
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…The role of the macrophage in antibody production has been described by Burnet (17) as an entirely passive one; by removing excess antigen the macrophages merely protect antibody-producing cells from the repeated exposure to antigen which might exert a deleterious effect on these cells. The opposite view is held by a number of other workers who consider the macrophage as an active producer of antibody (4,18). Still others believe that the maerophage solubilizes antigens and thereby merely enhances the stimulus to antibody-producing cells (19).…”
Section: Discussionmentioning
confidence: 98%
“…The role of the macrophage in antibody production has been described by Burnet (17) as an entirely passive one; by removing excess antigen the macrophages merely protect antibody-producing cells from the repeated exposure to antigen which might exert a deleterious effect on these cells. The opposite view is held by a number of other workers who consider the macrophage as an active producer of antibody (4,18). Still others believe that the maerophage solubilizes antigens and thereby merely enhances the stimulus to antibody-producing cells (19).…”
Section: Discussionmentioning
confidence: 98%
“…It is difficult to avoid the conclusions that macrophages are involved in the initiation of the' immune response to viruses because of their primary importance in the phagocytosis of foreign materials. It has been suggested that macrophageg turn into antibody-producing cells (54), and that macrophages themselves produce antibody (92). It has also been suggested that macrophages prepare antigen for antibodyproducing cells (58,129,134), and the evidence for this has sometimes been good.…”
Section: Immune Responsementioning
confidence: 99%
“…McKenna and Stevens [12] described that antibody production against T2 bacteriophages or bovine serum albumin were observed in cultures of mononuclear cells from rabbit peritoneal exudates. Jacherts On the other hand, Burnet [3] described the role of macrophages in antibody formation as an entirely passive one; by removing excess antigen the macrophages protect antibody forming cells from the repeated exposure to antigen.…”
Section: Discussionmentioning
confidence: 99%